2004
DOI: 10.2337/diacare.27.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Fasting Plasma Free Fatty Acids and Risk of Type 2 Diabetes

Abstract: OBJECTIVE -To evaluate whether plasma levels of free fatty acids (FFAs) are independently associated with incidence of type 2 diabetes. RESEARCH DESIGN AND METHODS-A case-cohort design was used to randomly select 580 incident cases of diabetes and 566 noncases from 10,275 African-American and white men and women in the Atherosclerosis Risk in Communities study, aged 45-64 years and without prevalent diabetes at the baseline exam. Incident diabetes was ascertained at three exams over 9 years of follow-up. FFA l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
2
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(105 citation statements)
references
References 43 publications
3
89
2
6
Order By: Relevance
“…The use of a mixed meal as a physiological stimulus, rather than insulin clamp techniques, allows assessment of normal physiological variations in diurnal NEFA concentrations. Such elevation of plasma NEFA concentrations may play an important role in the pathogenesis of type 2 diabetes [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…The use of a mixed meal as a physiological stimulus, rather than insulin clamp techniques, allows assessment of normal physiological variations in diurnal NEFA concentrations. Such elevation of plasma NEFA concentrations may play an important role in the pathogenesis of type 2 diabetes [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that obese subjects often exhibit elevated fatty acid levels due to the enlarged volume of adipose tissue (Opie & Walfish 1963, Jensen et al 1989). Furthermore, higher levels of fatty acids are related to a greater risk for diabetes (Paolisso et al 1995, Charles et al 1997, Pankow et al 2004, although the underlying mechanisms are not completely understood. However, elevated levels of free fatty acids induce insulin resistance in muscle and liver tissue by decreasing insulinstimulated glucose uptake and glycogenesis (Griffin et al 1999, Boden 2003, Wilding 2007.…”
Section: Patient Investigationsmentioning
confidence: 99%
“…To these effects could be added a long-term effect of elevated NEFA concentrations to impair glucosestimulated insulin secretion (Zhou & Grill, 1995;Carpentier et al 1999). These effects together may well explain why elevated NEFA concentrations are a predictor of future development of type 2 diabetes (Paolisso et al 1995;Charles et al 1997;Pankow et al 2004). The adverse effects of elevated NEFA concentrations also extend into other areas.…”
Section: The Metabolic Viewpointmentioning
confidence: 99%